2010
DOI: 10.1021/es903884a
|View full text |Cite
|
Sign up to set email alerts
|

Options for Near-Term Phaseout of CO2 Emissions from Coal Use in the United States

Abstract: The global climate problem becomes tractable if CO(2) emissions from coal use are phased out rapidly and emissions from unconventional fossil fuels (e.g., oil shale and tar sands) are prohibited. This paper outlines technology options for phasing out coal emissions in the United States by approximately 2030. We focus on coal for physical and practical reasons and on the U.S. because it is most responsible for accumulated fossil fuel CO(2) in the atmosphere today, specifically targeting electricity production, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…While most of the highly nuclear-dependent countries have affirmed their plans to continue development of nuclear power after the Fukushima accident, several have announced that they will either temporarily suspend plans for new plants or completely phase out existing plants . Serious questions remain about safety, proliferation, and disposal of radioactive waste, which we have discussed in some detail elsewhere …”
Section: Introductionmentioning
confidence: 99%
“…While most of the highly nuclear-dependent countries have affirmed their plans to continue development of nuclear power after the Fukushima accident, several have announced that they will either temporarily suspend plans for new plants or completely phase out existing plants . Serious questions remain about safety, proliferation, and disposal of radioactive waste, which we have discussed in some detail elsewhere …”
Section: Introductionmentioning
confidence: 99%
“…17 CSP plants (together with low-cost TES) generally present Global Warming Potential (GWP) of less than 40 g CO 2eq /kWh and Energy Payback Time (EPBT) less than 1 year, 17 indicating significantly reduced environmental impacts compared to conventional power plants based on fossil sources. 18,19 Relatively fewer LCA works in the literature include or focus on the TES materials/systems for CSP plants. In terms of TES materials, it has been reported that the environmental impacts could be reduced by switching from synthetic molten salts to mined salts, 20,21 to recycled industrial ceramics 22 or to concrete).…”
Section: Of 11mentioning
confidence: 99%
“…from construction to decommissioning and therefore includes maintenance periodic component replacement plus machinery use). The initial "emergy" (intrinsic energy stored in raw materials) also known as embodied energy has been excluded (Kharecha, Kutscher et al 2010).…”
Section: Inputsmentioning
confidence: 99%